Diversity of migration strategies among great frigatebirds populations. (10th February 2017) - Weimerskirch, Henri; Borsa, Philippe; Cruz, Sebastian; de Grissac, Sophie; Gardes, Lionel; Lallemand, Joëlle; Corre, Matthieu Le; Prudor, Aurélien
Abstract : Migratory behavior varies extensively between bird taxa, from long distance migration to purely sedentary behavior. Variability in migratory behavior also occurs within taxa, where individuals within some species, or even populations, show mixed strategies. The same variability occurs in seabird species. We examined the migratory behavior of distinct populations of great frigatebirds Fregata minor in three distant oceanographic basins. Great frigatebird populations showed extensive variation in post‐breeding migratory behavior. Birds from Europa Island (Mozambique Channel) made long‐distance migration to numerous distinct roosting sites in the Indian Ocean, New Caledonia birds made shorter distance migrations to roosting sites in the southwestern Pacific Ocean, and Galapagos birds were resident within the archipelago year round. Juvenile birds from Europa Is. and New Caledonia dispersed widely whereas Galapagos juveniles were resident year round. The migratory behavior of Europa Is. and New Caledonia resulted in complete separation of foraging grounds between breeding adults, non‐breeding adults, and juveniles, whereas in the Galapagos the overlap was complete. We suggest that population variability in migratory behavior may have arisen because of different environmental conditions at sea, and also depends on the availability of suitable roosting sites on oceanic islands. The results also highlight the capacity of frigatebirds to remain airborne most of the time even outside the breeding season when they have to molt.